논어 화제구의 해석과 교육(1) - ‘활동(DO)’ 사건의미 표시구의 예를 중심으로 - 김종호; Kim Jong Ho (Journal of Sinology and China Studies, 2019)
The Chinese language is a topic-prominent language and the ancient form of the language is not an exception. This literature examines the theta roles and cases of the arguments by setting sentence structures regarding ‘TopP’, which marks the eventuality meaning of ‘DO’, from the Analects of Confucius. Summary of the analysis is as follows: 1. Like the contemporary Chinese, ancient Chinese has two topic types; one is a base-generated topic(so called dangling topic) and the other is a topic generated by the interior movement in the TP. 2. The sentence structure of TopP from the Analects of Confucius that marks the eventuality meaning of ‘DO’ can be divided into seven categories which are: T+S+V+O’, ‘T+ES+V+EO’, ‘T+ES+V+EO’, ‘T+S+V+EC’, ‘T+ES+V+C’, ‘T+ES+V+O+C’, ‘T+S+V+EO+C’. 3. The predicate(V-v) of TopP from the Analects of Confucius that marks the eventuality meaning of ‘DO’ has a meaning characteristics of [+ will] and [+ progressive]. 4. The subject of TopP from the Analects of Confucius that marks the eventuality meaning of ‘DO’ is assigned a thematic role of an < agent >, and the object is assigned a thematic role of a < theme >. 5. The complement of TopP from the Analects of Confucius that marks the eventuality meaning of ‘DO’ is composed of overt preposition head and its complements, which receives diverse thematic roles from the preposition. However, it does not have a direct selective relationship but an indirect relationship with the main verb of the sentence. 6. Every argument, which is the subject, object, complement, and adverb, of TopP from the Analects of Confucius that marks the eventuality meaning of ‘DO’ can theoretically be moved in front of the subject and be topicalized. 7. The topic phrase from the Analects of Confucius that marks the eventuality meaning of ‘DO’ is derived in the order of predicate(V-v), object, complement, adjunct, subject, and topic, but when interpreting it in Korean it is in inverse order, which is in the order of topic, subject, adjunct, complement, object and predicate(V-v).